SISTEM INFORMASI DROPSHIP SI DROP MODEL PROTOTYPE PADA UMKM BINAAN PONTIANAK CREATIVE ASSOCIATION (PCA) - Reza Maulana; Yoki Fimansya; Fajar Akbar Wirand (Jurnal Informatika Kaputama (JIK), 2023)
The need for goods has increased drastically, currently there are many online-based trade innovations or e-commerce which is a program created to make this easier. Pontianak Creative Association (PCA) really needs an information system that can support and facilitate coaching for MSME actors, and can open job opportunities for business actors who want to sell with minimal capital. Currently, Pontianak Creative Association (PCA) is only a creative industry association engaged in multimedia, design, animation, and MSME coaching. The existing system at the Pontianak Creative Association (PCA) is still carried out manually, starting from recording MSME data, to storing other data related to the coaching process, and there is no application of the coaching. The system is designed by applying a prototype model and using data collection methods in research. The information system is the best solution to solve the problems that exist in this association / institution, and with a computerized program, an effective and efficient coaching activity can be achieved in supporting coaching at this institution, and it is very possible that in the future this program can solve problems in MSMEs and for dropshipping actors who want to dropship products from MSMEs.